PERAN INSENTIF PAJAK DALAM MENDORONG PERTUMBUHAN USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) - Moh. Abdurrosyid; Patriandari Patriandari; Sari Mujiani (POLITEKNIK LP3I JAKARTA, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the Indonesian economy as labor absorbers, drivers of economic activity, and supporters of national economic growth. However, various obstacles such as limited capital, low access to financing, and high operational costs often hinder business development. One of the government's efforts to support MSME growth is through the provision of tax incentives. This study aims to analyze the role of tax incentives in encouraging MSME growth and identify various factors that support and hinder the effectiveness of these policies. The study used a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and documentation with MSME actors and related parties who understand the implementation of tax incentive policies. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results show that tax incentives have a positive impact on MSME growth by reducing operating expenses, increasing working capital, increasing turnover, developing production capacity, and increasing business competitiveness. Tax incentives also encourage MSME actors to innovate products and expand their marketing reach. However, the effective utilization of tax incentives still faces various obstacles, such as low tax literacy, inadequate policy dissemination, administrative complexity, and limited access to digital tax services. Research findings indicate that business actors' level of understanding of tax policies is a critical factor in determining the successful utilization of tax incentives.